Polimorfismos de nucleotídeo único dos genes MLH1 E MSH2: susceptibilidade ao câncer de mama - Santos, Anderson Felix dos (2019)
Several genes have already been associated with breast cancer development and about 60% of cases cannot be explained by mutations in BRCA1 and BRCA2. For this reason, further studies have been developed indicating that polymorphic changes in mismatch repair mechanism genes, especially in MLH1 and MSH2 genes, constitute a risk factor for the development of sporadic tumors. Based on this information, the study aimed to genotype the SNH rs560246973 (T> C), rs2303425 (-118 T> C) SNH gene rs565410865 (G> T) in paraffin tissue samples from patients diagnosed with breast cancer. . One hundred paraffin tissue samples from patients from Paraíba State with histopathological diagnosis of breast cancer were analyzed. After DNA extraction as proposed by Shang Rong-Shi et al., And primer design by in silico validation, the results were obtained by applying the Dideoxy Single Allele-Specific PCR method and analyzed using Chi-square and exact tests. Fisher's, with a significance level of 5%. The analyzes suggest that the rs565410865 and rs560246973 SNPs, located in the intronic region of the MLH1 and MSH2 genes, respectively, were statistically associated with breast cancer in the analyzed samples (X² 100/100 and P-value 0.0001). In contrast, genotyping the SNP rs2303425, located in the promoter region of the MSH2 gene, showed no statistical significance, indicating its non-association with breast cancer (X² 0.7561 and P-value 0.3845). In this sense, rs565410865 and rs560246973 SNPs are potential molecular markers for increased susceptibility to breast cancer development.